Global perspectives, local solutions: Improving human-predator coexistence through collaboration, meaningful experiences and cross-cultural knowledge - Almuna, Rocio; Ramalho, Cristina E.; Ibarra, José Tomas; Speldewinde, Peter; Hopper, Stephen D. (My University, 2025)
Human-predator coexistence is a complex and dynamic relationship influenced by a variety of social-ecological factors. Recognising conflict as an inherent aspect of coexistence, rather than merely a problem to be solved, is crucial. This literature review examines how a range of factors contributes to human coexistence with predators. A systematic review of 76 peer-reviewed articles from 33 countries provides valuable insights into the complexities associated with these factors across different contexts. Collaboration among social actors is crucial for addressing cultural tensions, increasing trust in state agencies and reaching agreements for coexistence practices. While material benefits (e.g. ecotourism, financial compensation) are often emphasised, relational and intrinsic values, emotions and meaningful personal experiences play an even greater role in fostering coexistence. Acknowledgment of positive predator attributes, mutual benefits, cultural significance and deep human-wildlife connections may help shape perceptions of predators in a culturally informed manner. Further appropriate and respectful cross-cultural research that amplifies Indigenous voices and knowledge is essential for understanding the nuances of human-predator interactions across diverse socio-economic and ecological contexts. Comprehensive management to improve human-predator relationships needs to consider ecological contexts alongside the cultural norms and priorities of local communities. This approach will enable legitimate, situated and long-term coexistence practices and solutions.Read the free Plain Language Summary for this article on the Journal blog. La coexistencia entre humanos y depredadores es una relación compleja y dinámica influenciada por una variedad de factores socioecológicos. Reconocer el conflicto como un aspecto inherente de la coexistencia, en lugar de verlo solo como un problema a resolver, es fundamental. Esta revisión de la literatura examina cómo una serie de factores contribuyen a la tolerancia y la coexistencia entre humanos y depredadores. Una revisión sistemática de 76 artículos revisados por pares de 33 países proporciona valiosas perspectivas sobre los matices asociados con estos factores en diferentes contextos. La colaboración entre los actores sociales es crucial para abordar las tensiones culturales, aumentar la confianza en las agencias estatales y alcanzar acuerdos para prácticas de convivencia. Aunque se suelen enfatizar los beneficios materiales (por ejemplo, ecoturismo, compensación económica), los valores relacionales e intrínsecos, las emociones y las experiencias personales significativas juegan un papel aún más importante en el fomento de la tolerancia. El reconocimiento de los atributos positivos de los depredadores, los beneficios mutuos, la importancia cultural y las profundas conexiones humanas con la fauna pueden ayudar a moldear las percepciones de los depredadores de manera culturalmente informada. Es esencial realizar más investigaciones interculturales adecuadas y respetuosas que amplifiquen las voces y el conocimiento indígena para comprender los matices de las interacciones entre humanos y depredadores en diversos contextos socioeconómicos y ecológicos. Una gestión integral para mejorar las relaciones entre humanos y depredadores debe considerar los contextos ecológicos junto con las normas culturales y prioridades de las comunidades locales. Este enfoque permitirá prácticas y soluciones de convivencia legítimas, situadas y a largo plazo.
Keywords: carnivores; interactions; raptors; social-ecological landscapes; tolerance